The role of mitochondrial DNA copy number in autoimmune disease: a bidirectional two sample mendelian randomization study - Liu, Zhekang; Fu, Qingan; Shao, Yijia; Duan, Xinwang (Frontiers in Immunology, 2024)
Background：Mitochondrial DNA (mtDNA) plays an important role in autoimmune diseases (AD), yet the relationship between mitochondria and autoimmune disease is controversial. This study employed bidirectional Mendelian randomization (MR) to explore the causal relationship between mtDNA copy number and 13 ADs (including ankylosing spondylitis [AS], Crohn's disease [CD], juvenile rheumatoid arthritis [JRA], polymyalgia rheumatica [PMR], psoriasis [PSO], rheumatoid arthritis [RA], Sjogren's syndrome [SS], systemic lupus erythematosus [SLE], thyrotoxicosis, type 1 diabetes mellitus [T1DM], ulcerative colitis [UC], and vitiligo)Methods: A two-sample MR analysis was performed to assess the causal relationship between mtDNA copy number and AD. Genome-wide association study (GWAS) for mtDNA copy number were obtained from the UK Biobank (UKBB), while those associated with AD were sourced from the FinnGen Biobank. Inverse variance weighting (IVW) was the primary analysis method, complemented by three sensitivity analyses (MR-Egger, weighted median, weighted mode) to validate the results.Results: IVW MR analysis identified significant associations between mtDNA copy number and CD (OR=2.51, 95% CI 1.56-4.22, P<0.001), JRA (OR=1.87, 95% CI 1.17-7.65, P=0.022), RA (OR=1.71, 95%CI 1.18-2.47, P=0.004), thyrotoxicosis (OR=0.51, 95% CI0.27-0.96, P=0.038), and T1DM (OR=0.51, 95% CI 0.27-0.96, P=0.038). Sensitivity analyses indicated no horizontal pleiotropy.Conclusions：Our study revealed a potential causal relationship between mtDNA copy number and ADs, indicating that these markers may be relevant in exploring new therapeutic approaches.